KONTRIBUSI RED FLAGS DALAM PRAKTIK MANAJEMEN LABA DAN DAMPAKNYA PADA KEANDALAN LABA - Titi Purbo Sari; Purbawati; Hendra Wijaya; Nasron Alfianto (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2026)
The rapid growth of an increasingly competitive business climate requires companies to obtain quality financial information as a tool for generating high profits. One of the steps taken is profit management practices that aim to make profits look better and meet expectations. Both accrual and real profit management can reduce the ability of profits to predict future performance and reflect the real economic condition of the company. The integrity of financial statements is compromised when earnings management leads to accounting fraud and does not comply with generally accepted accounting standards, triggering red flags. The purpose of this study is to develop and find empirical evidence of the contribution of red flags in earnings management practices to earnings quality. The research sample consisted of 252 property and real estate companies listed on the Indonesia Stock Exchange for the period 2021-2024. The research data was analyzed using panel data regression methods. The research results provide a different perspective, namely that accrual earnings management can actually increase earnings reliability, while real earnings management can actually reduce earnings quality. Red flags do not contribute to the relationship between both accrual and real earnings management and earnings quality.